The relation of art and industry - McCrone, Sara Grace (My University, 1904)
Introduction: The mention of art generally conveys the idea of something beautiful and perhaps grand, but it is not generally thought that the word conveys anything whatever in they way of usefulness. It is the usefulness of art and its relation to the various industries that we would discuss. The so called fine arts in all things beauty, glory and usefulness are not to be considered. Kenyon Cox says “The highest aim of art is to make some useful thing beautiful.” This is at least the part of the scope of art that comes nearest the common people and that which should be the most interesting to every one. The usefull things are the homely things of life, and the things with which we come in contact every day. But these things may be beautiful while they are usefull. And there is always a chance to beautify even the most homely article…
Citation: McCrone, Sara Grace. The relation of art and industry. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Art; Industry; Practical Applications; Theses; Manuscripts (documents)